Feedback Model to Support Designers of Blended-Learning Courses - Hummel, Hans G. K. (International Review of Research in Open and Distributed Learning, 2006)
Although extensive research has been carried out, describing the role of feedback in education, and many theoretical models are yet available, procedures and guidelines for actually designing and implementing feedback in practice have remained scarce so far. This explorative study presents a preliminary six-phase design model for feedback (6P/ FB-model) in blended learning courses. Each phase includes leading questions and criteria that guide the designer. After describing the model, we report research into the usability and quality of draft versions of this model. Participants in both a small usability pilot and an expert appraisal survey rated and commented on the model. We conclude that the overall quality of the model was perceived as sufficient, although experts recommended major revisions before the model could actually be used in daily practice.